# Show that x = - 3 is a solution of x2 + 6x + 9 = 0.

If x = - 3 is a solution then it must satisfy the equation

x2 + 6x + 9 = 0

LHS = x2 + 6x + 9

= ( - 3)2 + 6. - 3 + 9

= 9 - 18 + 9

= 18 - 18

= 0 = RHS

Thus x = - 3 is a solution of the equation

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Knowing the Nature of Roots44 mins
Take a Dip Into Quadratic graphs32 mins
Foundation | Practice Important Questions for Foundation54 mins
Nature of Roots of Quadratic EquationsFREE Class
Getting Familiar with Nature of Roots of Quadratic Equations51 mins
Quadratic Equation: Previous Year NTSE Questions32 mins
Champ Quiz | Quadratic Equation33 mins
Balance the Chemical Equations49 mins
Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses